2020
DOI: 10.1111/joor.13101
|View full text |Cite
|
Sign up to set email alerts
|

Increased somatosensory amplification is associated with decreased pressure pain thresholds at both trigeminal and extra‐trigeminal locations in healthy individuals

Abstract: Background: The diagnosis of temporomandibular disorders (TMD) is based on patient history and physical examination, and may require medical imaging. Masticatory muscle palpation is essential to make a diagnosis of TMD. However, the response of masticatory muscles to mechanical pressure stimuli depends on many physical and psychological factors. Objective: This study aimed at determining the impact of somatosensory amplification (SSA)-an estimate of somatic awareness and bodily hypervigilance-on pressure pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
0
7
1
Order By: Relevance
“…Remarkably, we did not observe a statistically significant difference in PPT between cases and controls, despite low-impact TMD cases presenting numerically lower mean PPT in the face in visits 1 and 2. This finding is in contrast to a body of literature reporting decreased PPT over the masseter muscles in TMD cases when compared to controls 88 90 , however this discrepancy has also been reported previously by others 91 and it has been recently suggested that somatosensory amplification may act as confounder for decreased PPT 92 . We observed that jaw pain ratings across visits were correlated between each other in the low-impact TMD group, while in the high-impact TMD group significant positive correlations were found between PPT across visits (both face and hand sites), which could suggest that pain-related impact status differentially contributes to the longitudinal pattern for clinical and experimental pain in each of these TMD groups.…”
Section: Discussioncontrasting
confidence: 97%
“…Remarkably, we did not observe a statistically significant difference in PPT between cases and controls, despite low-impact TMD cases presenting numerically lower mean PPT in the face in visits 1 and 2. This finding is in contrast to a body of literature reporting decreased PPT over the masseter muscles in TMD cases when compared to controls 88 90 , however this discrepancy has also been reported previously by others 91 and it has been recently suggested that somatosensory amplification may act as confounder for decreased PPT 92 . We observed that jaw pain ratings across visits were correlated between each other in the low-impact TMD group, while in the high-impact TMD group significant positive correlations were found between PPT across visits (both face and hand sites), which could suggest that pain-related impact status differentially contributes to the longitudinal pattern for clinical and experimental pain in each of these TMD groups.…”
Section: Discussioncontrasting
confidence: 97%
“…These researchers highlighted that somatosensory amplification tends to be greater in patients with facial pain than in pain-free cases ( 73 ). However, recent studies revealed no relationship between severity of somatosensory amplification and the frequency of oral behaviors and trait anxiety ( 75 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, such influence was not observed in a spinal area. This is a curious finding, as previous case–control studies demonstrated lower PPT values in TMD patients, 71,72 both in trigeminal and spinal areas. This could indicate a generalised hypersensitivity of the central nervous system 73,74 .…”
Section: Discussionmentioning
confidence: 83%